2011
DOI: 10.1017/s1092852912000211
|View full text |Cite
|
Sign up to set email alerts
|

Self-Harm in Prisoners

Abstract: Self-harm is associated with critical behaviors such as violence, substance abuse and suicide attempts, which represent major critical problems in contention environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 0 publications
2
25
2
Order By: Relevance
“…This study sought to identify independent predictors of self-directed aggression (suicidal behavior and/or self-mutilation), in a large sample of incarcerated Italian men. Both suicidal behavior and self-mutilation are more common in prisoners than the general population and these behaviors are frequently comorbid (Carli et al 2011a;Fazel & Danesh 2002;Horton et al 2014;Jenkins et al 2005;Stanley et al 2001). Indeed, one third of our sample with self-directed aggression had a lifetime history of both suicidal behavior and self-mutilation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study sought to identify independent predictors of self-directed aggression (suicidal behavior and/or self-mutilation), in a large sample of incarcerated Italian men. Both suicidal behavior and self-mutilation are more common in prisoners than the general population and these behaviors are frequently comorbid (Carli et al 2011a;Fazel & Danesh 2002;Horton et al 2014;Jenkins et al 2005;Stanley et al 2001). Indeed, one third of our sample with self-directed aggression had a lifetime history of both suicidal behavior and self-mutilation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that 77% of US prisoners who attempted suicide had psychiatric disorders compared with 15% in the general prison population (Goss et al , 2002). A few studies have shown that self-mutilation is also common in prisoners (Carli et al , 2011a, Horton et al , 2014). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that specific risk factors, such as violent behaviour in prison, psychiatric diagnosis, substance abuse and previous suicide attempts are associated with self-harm in prison 2. Fifty per cent of prisoners who die by suicide have a history of self-harm3 and longitudinal studies are needed to understand which prisoners with self-harm are more likely to complete suicide.…”
Section: What Is Already Known On This Topic?mentioning
confidence: 99%